2020
DOI: 10.1177/1010539520963643
|View full text |Cite
|
Sign up to set email alerts
|

An Age-Period-Cohort Analysis of Prevalence and Consultation Rate for Dyslipidemia in Japan

Abstract: This study involved an age-period-cohort analysis of the consultation rate and prevalence of dyslipidemia in Japan, based on Patient Survey data from 1999 to 2017 and open data of national database of health insurance claims and specific health checkups in Japan from 2013 to 2016. Our results showed that the consultation rates were lower than the prevalence, regardless of age, year, and sex, and particularly among middle-aged and male respondents. Additionally, both the consultation rate and prevalence increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In the present study, the association with dyslipidemias remains strong with the higher self-reported body silhouette (silhouettes: 6, 7, 8, and 9); this association persists after correcting the analysis by age, a variable that strongly influences the lipid profile in healthy patients [ 25 ]. Our findings might be attributed to the proxy measurement of adiposity performed by the self-reported body silhouette, as it has been reported that excessive body fat percentage is a main metabolic comorbidity associated with dyslipidemia.…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, the association with dyslipidemias remains strong with the higher self-reported body silhouette (silhouettes: 6, 7, 8, and 9); this association persists after correcting the analysis by age, a variable that strongly influences the lipid profile in healthy patients [ 25 ]. Our findings might be attributed to the proxy measurement of adiposity performed by the self-reported body silhouette, as it has been reported that excessive body fat percentage is a main metabolic comorbidity associated with dyslipidemia.…”
Section: Discussionmentioning
confidence: 86%
“…The trends of the age effects for triglycerides were particularly different depending on sex for the age group older than the 40s. Previous studies have indicated that an increase in the prevalence of dyslipidemia starting from the 50's age group is particularly evident for women in Japan [38]. Menopause leads to changes in the hormonal status, metabolism, and lipid profile [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The age-standardized prevalence of dyslipidemia aged ≥35 years during 2015-2017 in Inner Mongolia was 31.2%, and male sex and obesity were positively correlated with dyslipidemia [22]. Furthermore, a cohort study from Japan also showed that the prevalence of dyslipidemia was higher in men than in women and tended to increase with age [23]. In 2013, a large sample of 170287 urban and rural residents in 31 provinces showed that the standardized prevalence rate of diabetes mellitus in Chinese adults was 10.9%, with males (11.7%) higher than females (10.2%) [24].…”
Section: The Association Between Sua Levels and Hypertension Diabetes...mentioning
confidence: 97%